ALZHEIMERS's DISEASE: EPIDEMIOLOGICAL CHARACTERISTICS AND ITS PREVENTION - Grujicic, Jovan; Nikolic, Aleksandra (HEALTH CARE, 2021)
Alzheimer's disease is a progressive neurodegenerative brain disease that is of immense public health interest.  Worldwide, according to data from 2018, the approximated number of people living with Alzheimer's was at a minimum 50 million. In the United States, according to data from 2021, there were as many as 6.2 million people age 65 and over living with Alzheimer's. In the last 20 years, Alzheimer's disease is being recorded 145.2% more frequently as the cause of death, partially due to the cause of death being more accurately attributed, but mostly due to the growing frequency of Alzheimer's disease due to the aging of the population. Based on years of life lost(YLL), Alzheimer's disease was the fourth, according to years of life with disability (YLD) nineteenth and according to the sum indicator DALY (Disability Adjusted Life Years) sixth leading cause of burden amongst diseases in the USA in 2016. The nonmodifiable risk factors for developing Alzheimer's disease are age, genetics, and family history, while the modifiable risk factors are smoking, diabetes, midlife obesity, hypertension, prehypertension, high cholesterol, insufficient physical activity, unhealthy diet, shorter length of formal education, low level of mental stimulation at work, traumatic brain injury, poor sleep, alcohol abuse, and hearing impairment. It is estimated that by reducing the modifiable risk factors, 40% of cases of Alzheimer's dementia can be prevented or postponed. The biomarkers that can be used for early detection of this disease are beta-amyloid protein that forms beta-amyloid plaques, abnormal tau protein accumulated inside neurons, the existence of brain inflammation and atrophy. While we wait for researchers to find a cure for this illness, it is important to raise awareness of available screening methods for early detection of Alzheimer's disease and prevention opportunities.
Keywords: Alzheimers disease, epidemiology, prevalence, mortality, risk factors, biomarkers